POWER, METALLURGICAL AND CHEMICAL MECHANICAL ENGINEERING PHYSICAL DATA CODING USING POLARISING SPIN DEVICES - A. I. Dmitriev (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. Spin nanoelectronics facilitate fundamentally new ways of encoding and encrypting information implemented using photon spins in fibre-optic data transmission lines. The article discusses the possibility of creating a spin LED emitting circularly polarised light.Methods. In a spin LED, spin-polarised carriers are injected from a ferromagnetic contact combined with a quantum well.Results. Quantum selection rules for describing recombination establish a connection between the circular polarisation of light, emitted along the normal to the surface, and the spin polarisation of the electrons.Conclusion. Physical methods for coding and transmitting information by means of polarised spin devices using the spin degree of freedom are formulated. The configuration principles of a polarised radiation generator (spin LED) are proposed. The approach is based on a heterostructure containing the quantum well InGaAs / GaAs (luminescent layer) and the ferromagnetic layer GaMnAs. It is established that the quantum well emission line is split into two circularly polarised components, which opens up new possibilities for coding and transmission of information in fibre-optic data transmission lines by the methods of polarisation modulation. The circular polarisation of the photoluminescence from the InGaAs / GaAs quantum well is caused by the magnetisation of a nearby ferromagnetic GaMnAs layer. Acknowledgments The author is grateful to the employees of NIFTI UNN named after N.I. Lobachevsky Yu.A. Danilov and M.V. Dorokhin for samples, the employee of ISSP RAS S.V. Zaitsev for optical measurements, the employee of the Moscow State University of Railway Engineering (MIIT) V.P. Solov'ev for useful discussions. The work is partially supported by the grant of the Russian Foundation for Basic Research No. 16-07-00863a and the RF President's grant MK-5754.2016.3.